Reading Assistant for the Visually Impaired (International Journal of Current Engineering and Technology, 2015)
A Majority of the visually impaired use Braille for reading documents and books which are difficult to make and less readily available. This gives rise to the need for the development of devices that could bring relief to the agonizing tasks that the visually impaired has to go through. Due to digitization of books there are many excellent attempts at building a robust document analysis system in industries, academia and research labs, but this is only for those who are able to see. This project aims to study the image recognition technology with speech synthesis and to develop a cost effective, user friendly image to speech conversion system with help of Raspberry Pi. The project has a small inbuilt camera that scans the text printed on a paper, converts it to audio format using a synthesized voice for reading out the scanned text quickly translating books, documents and other materials for daily living, especially away from home or office. Not only does this save time and energy, but also makes life better for the visually impaired as it increases their independency.
Keywords: Raspberry Pi; OCR; Reading Assistant.